2007
DOI: 10.1142/s0217979207037326
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Goos-Hänchen Displacement in Total Internal Reflection

Abstract: Since the Goos-Hänchen (GH) effect is the displacement of the totally reflected beam at a dielectric interface from the position prediction by geometrical reflection, the concept of GH displacement is applicable only when the reflected beam retains the shape of the geometrically reflected or incident beam. The necessary and sufficient condition has been advanced for the totally reflected beam to retain the shape of the incident beam. Numerical simulations have been performed to confirm this condition. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Furthermore, the scanning output coupler provides a means for calculating the precise angle of incidence on the prism surface via the mode splitting between s-and p-polarized light. From these measurements we find that θ i − θ c ≈ 1.3 • , which is significantly larger than the beam divergence of 0.19 • (as calculated using the method outlined by Shi et al [15]). indicating that both larger penetration depths and scattering effects can easily be accessed by reducing the angle of incidence at the interface.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, the scanning output coupler provides a means for calculating the precise angle of incidence on the prism surface via the mode splitting between s-and p-polarized light. From these measurements we find that θ i − θ c ≈ 1.3 • , which is significantly larger than the beam divergence of 0.19 • (as calculated using the method outlined by Shi et al [15]). indicating that both larger penetration depths and scattering effects can easily be accessed by reducing the angle of incidence at the interface.…”
Section: Discussionmentioning
confidence: 51%
“…A larger ε gives a larger loss for a TIR grating spectrometer. It should be mentioned that the theories developed in [23][24][25] lead to contradictory or incomplete results according to Eqs. (4) and (5).…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Through decades' investigations by researchers (Artmann, 1948;Renard, 1964;Carniglia, 1976;McGuirk and Carniglia, 1977;Lai et al, 1986;Shi et al, 2007;Bliokh and Aiello, 2013), several approximated mathematical expressions have been derived for calculating the GHS by using the reflection coefficient, the energy flux vector, or the momentum. People found that albeit the GHS is typically a beam effect which appears for beams with finite cross-sections, the calculations of GHS can be achieved by computing plane waves' phase variations of the reflection coefficient.…”
Section: Reflection Coefficients Ghs and Pdmentioning
confidence: 99%